Synthesis of pyrazolo[4, 3-f]thieno[3, 2-b]quinoline-10-carbonitrile: a new heterocyclic system exhibiting strong fluorescence. (1st July 2013) - Hoseini-Hesar, Toktam; Pordel, Mehdi; Roshani, Mina; Shams, Alireza
Synthesis of new substituted pyrazolo[4, 3-f]thieno[3, 2-b]quinoline-10-carbonitriles has been accomplished by the nucleophilic substitution of hydrogen in 5-nitroindazole derivatives. The synthesised compounds revealed fluorescent properties and the characteristics of the compounds were studied using UV absorption and emission spectroscopy.